AN EXPERIMENTAL INVESTIGATION OF AQUEOUS SOLUTION OF AMMONIUM BASED IONIC LIQUID FOR CO2 /CH4 SEPARATION AND APPLICATION - KARTIKAWATI, NUR ANI (2018)
Conventional CO2 capture solvents are pooly efficient due to their low CO2 loading capacity, corrosive nature, thermal and oxidative degradation, high regeneration energy requirement, and high volatility. To replace these conventional solvents, tetrabutylammonium hydroxide (TBAOH) is investigated as a potential CO2 capture solvent due to its effective corrosion inhibition properties, high thermal stability, and negligible volatile nature.